Workers' desire for union participation in the wake of globalisation - Katuwal, Shyam (2006)
TThis paper identifies the extent of unionization, union participation and factors affecting workers' desire to participate in union. In spite of the world-wide erosion of trade union membership in the context of economic globalization, this paper reveals a high degree of unionisation with intense interest of workers towards trade unionism, but thin per union membership density due to fragmentation of unions on political grounds. Economic and material benefits, security, solidarity, alienation along with job dissatisfaction and political consciousness have emerged as the important factors in determining workers' desire for union participation. Less confidence on trade unions and their leaders, fear of victimisation and multiplicity of unions in political background appear to be major factors creating apathetic attitudes of workers towards unionism. Implications of the findings are discussed in the light of improving unionisation and participation. - Reproduced.
Keywords: Labour; Globalizations; Trade unions